Fenologia disponibilidade de biomassa e valor nutritivo do caranguejo (Calliandra depauperata benth) - Pará, Helena Célia Bezerra (1984)
An experiment was conducted at the Fazenda Pau Preto, Parambu County, Inhamuns sertão, 400km southwest of Fortaleza, Ceará, Brazil. A 900 sq.meter area with the native vegetation dominated by Carquejo (Calliandra depauperata Benth) was protected from the domestic livestock by a barbed wire fence. [...]